Exploring the Use of Probicon L28 and BIOPLUS 2B as Direct-Fed Microbials to Reduce Salmonella and Shiga Toxin-Producing Escherichia coli in Market Pigs - Jimeng Bai; Macie E. Reeb; Mike D. Tokach; Jordan T. Gebhardt; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jessie L. Vipham; Qing Kang; John W. Schmidt; Dayna M. Brichta-Harhay; Joseph M. Bosilevac; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
Pigs are hosts forSalmonellaand Shiga toxin-producingEscherichia coli(STEC) and these pathogens can commonly be isolated from the pig farm environment. Pigs can carry pathogens to the abattoir and contaminate pork products, posing a risk to public health. Identifying an intervention that effectively reduces pathogens in commercial pigs before harvest is imperative. Due to the need for effective pre-harvest interventions in the pig industry, the objective of this study was to investigate BIOPLUS 2B (Bacillus licheniformisandBacillus subtilis) and Probicon L28 (Lactobacillus salivariusL28) as pre-harvest interventions to reduceSalmonellaand STEC in commercial growing-finishing pigs. Two groups of pigs (group 1, N = 294; group 2, N = 356, initial body weight = 106.6 lb) were fed a standard corn-soybean meal (SBM) finishing diet according to the following treatments: Probicon L28 supplementation through water lines at 1.0 × 106 CFU/head/day (Probicon); BIOPLUS 2B supplemented at 3.0 × 109 CFU/head/day (BIOPLUS 2B); and a control with no added probiotic (Control). With each group of pigs, 12 pens were used per treatment (N = 24 total), for a total of 36 pens per group (N = 72 pens total). Each group was sampled upon arrival/baseline, midway through the grow-finish phase/6 weeks post-placement, and prior to loadout/13 weeks post-placement to collect fecal samples (4 pigs/pen), boot covers (2/pen), and ropes (1/pen). Market pigs were followed to the abattoir and superficial inguinal lymph nodes (SILNs) were collected. All samples were analyzed for STEC (stx, eaegenes, and O157:H7, and O26, O111, O121 O45, O103, and O145 serogroups) andSalmonellausing the BAX System (real-time polymerase chain reaction). Overall,Salmonellaand O111 prevalence was very low for all sample types, andEscherichia coliO157:H7 was not detected in any samples throughout the study. When compared to the control, there was no evidence (P>0.05) that BIOPLUS 2B and Probicon L28 impacted the prevalence of STEC (stxandeaegenes) or serogroups O26, O121, O45, O103, and O145 in feces, boot covers, ropes, and SILNs of market pigs.
Keywords: Escherichia coli; Salmonella; probiotics; Probicon L28; BioPlus 2B; market pigs; pre-harvest interventions